Safety of oral ivermectin during pregnancy: a systematic review and meta-analysis - Patricia Nicolas, MSc; Marta F Maia, PhD; Quique Bassat, ProfPhD; Kevin C Kobylinski, PhD; Wuelton Monteiro, PhD; N Regina Rabinovich, MD; Clara Menéndez, ProfPhD; Azucena Bardají, PhD; Carlos Chaccour, PhD (Elsevier, 2020)
Summary: Background: About 3·7 billion doses of ivermectin have been distributed in mass drug administration (MDA) campaigns globally over the past 30 years. At 10-100 times higher than current human doses, ivermectin is a known teratogen in mammals. During these campaigns with recommended doses, pregnant women might be inadvertently exposed. We therefore aimed to evaluate the existing evidence for serious and non-serious adverse events after ivermectin exposure in pregnant women. Methods: For this systematic review and meta-analysis, we searched relevant databases and trial registry platforms on July 15, 2018, for randomised controlled trials (RCTs) and observational studies that reported adverse events in pregnant women. We did not use language or date restrictions. Outcomes of interest were spontaneous abortions, stillbirths, congenital anomalies, and neonatal death (serious adverse events), as well as maternal morbidity, preterm births, and low birthweight (adverse events). The risk of bias was assessed using the Newcastle-Ottawa Scale for observational studies and the Cochrane Risk of Bias Tool for RCTs. We did the meta-analysis of observational studies and RCTs separately. The quality of evidence was assessed using the GRADE approach. The study protocol is registered with PROSPERO, protocol CRD42016046914. Findings: We identified 147 records, of which only five observational studies and one RCT were included for quantitative analysis; these studies were published between 1990 and 2008, and were done in six African countries. 893 women with 899 pregancy outcomes were included, of whom 496 pregnant women (500 pregnancy outcomes) received ivermectin inadvertently during MDA campaigns in the observational studies and 397 pregnant women (399 pregnancy outcomes) purposely received ivermectin as part of the open-label RCT. No study reported neonatal deaths, maternal morbidity, preterm births, or low birthweight. It is unclear whether exposure to ivermectin during pregnancy increases the risk of spontaneous abortions and stillbirths (odds ratio [OR] 1·15 [95% CI 0·75-1·78] with very low certainty of evidence for the four observational studies and 0·62 [0·18-2·14] with very low certainty of evidence for the RCT) or congenital anomalies (OR 1·69 [95% CI 0·83-3·41] with very low certainty of evidence for the five observational studies and 1·10 [0·07-17·65] with very low certainty of evidence for the RCT). Interpretation: There is insufficient evidence to conclude on the safety profile of ivermectin during pregnancy. Treatment campaigns should focus additional efforts on preventing inadvertent treatment of pregnant women. Funding: Unitaid.